STRATEGI PENYELESAIAN SENGKETA DALAM HAK TANGGUNGAN PEMBIAYAAN BERMASALAH PADA BANK MUAMALAT CABANG PADANGSIDIMPUAN - Ansor, ANSOR SYAPUTRA SIREGAR (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2023)
Financing is one of the products of Bank Muamalat Indonesia with an interest-free financing installment scheme that uses a Mudharabah financing contract. The occurrence of problem financing cases in financial transactions can be categorized as a form of default because the debtor cannot fulfill the obligation to pay off his debt to the creditor. The purpose of this study is to explain the strategy for resolving troubled financing disputes at Bank Muamalat Indonesia. This type of research uses qualitative literature study. The results of this study are the strategy of Bank Muamalat Indonesia in resolving disputes using non-litigation channels with steps, billing, rescheduling, re-requirements, rearrangements, and with execution parties. Settlement of disputes using separate execution is the final step in resolving non-performing financing disputes.